Influencing and protective factors of suicidal ideation among older adults. (25th July 2016) - Huang, Li‐Bi; Tsai, Yun‐Fang; Liu, Chia‐Yih; Chen, Ying‐Jen
Abstract: Suicide is a global issue, but few studies have explored the triggers and psychological feelings of suicidal ideation in older adults. A qualitative design with face‐to‐face semistructured interviews examined the experience of suicidal ideation in adults aged 65 years and older. A purposive sampling of 32 outpatients with suicidal ideation from a medical centre in northern Taiwan participated. Interview data identified three themes: triggers for suicidal ideation, contributing psychological changes, and factors of adaptive response. The triggers for suicidal ideation included physical discomfort, loss of respect and/or support from family, impulsive emotions due to conflicts with others, and painful memories. Psychological changes contributed to suicidal ideation: feelings of loneliness, a sense of helplessness, or lack of self‐worth. Participants described adaptive responses that acted as protective factors of suicidal ideation: support from family and friends, control of emotions, establishing a support network, comfort from religion, medication, and focussing on the family. Mental health nurses and clinicians should incorporate evaluations of stressful life events and psychological changes into a screening scale for older adults to improve detection of those at risk for suicide. Teaching coping strategies could provide timely interventions to secure the safety of this older population of adults.